Damage to eucalyptus caused by cattle in integrated crop-livestock-forestry systems with different tree arrangements in western São Paulo State, Brazil - Andrighetto, Cristiana [UNESP]; Mateus, Gustavo Pavan; dos Santos, Wanderley; de Moraes, Mario Luiz Teixeira [UNESP]; Lupatini, Gelci Carlos [UNESP]; da Silva, Vanderley Porfírio; Sekiya, Bianca Midori Souza [UNESP]; Duarte, Júlia Paschoareli Ferro [UNESP]; Pinto, Beatriz Vanni Grandjean [UNESP]; da Silva, Jonas Reina [UNESP] (Springer Nature, 2024)
The objective of this study was to evaluate the damage caused to trees by beef cattle in integrated crop-livestock-forestry (ICLF) systems with different tree arrangements. The treatments evaluated were the ICLF-1L system, with single lines of eucalyptus (187 trees ha−1), and the ICLF-3L system, with three lines of eucalyptus (446 trees ha−1). The experimental design consisted of randomized blocks with four replications. The eucalyptus clone I-224 and Nellore cattle breed were used for this study. The damage caused by cattle to eucalyptus was classified as follows: Tb, trunk breakage; Ti, trunk injury reaching the wood by removing the cambium tissue; Bb, breakage branches greater than 2 cm in diameter; Bi, bark injury without reaching the cambium; Bt, breakage of thin branches and browsing on leaves; and Di, lesions greater than 5 cm in diameter. The damage score was calculated for each tree by the sum of grade the damage that cattle caused to the tree: Tb = 10.0; Ti = 4.0; Bb = 2.0; Bi = 1.5; Bt = 1.0; and Di = 1.0. The diameter at breast height (DBH), height and wood volume of the trees were also evaluated. The frequencies of Ti, Bb and Di were greater in the ICLF-1L system than in the ICLF-3L system (P < 0.05); in contrast, the frequencies of Bt and Bi were greater in the ICLF-3L system. The damage score was greater in the ICLF-1L system (6.61; P < 0.05) than in the ICLF-3L system (4.60). The height was greater in the ICLF-3L system (P < 0.05), and the DBH and individual wood volume did not differ between the systems (P > 0.05). Cattle cause damage to eucalyptus trees regardless of tree arrangement (ICLF-1L and ICLF-3L), but the damages were greater in the ICLF-1L system. Although the damages were more severe in ICLF-1L, tree growth and wood production were the same in both systems. Additional studies should be conducted to assess the impacts of livestock damage in wood quality.
Keywords: Agrosilvopastoral system; Eucaliptus urograndis; Nellore; Wood